2019
DOI: 10.1515/mammalia-2018-0096
|View full text |Cite
|
Sign up to set email alerts
|

Movement and use of environmental structures, climbing supports and shelters by Akodon montensis (Sigmodontinae, Rodentia) in the Atlantic Forest of southern Brazil

Abstract: Movements under environmental structures and on supports, and the use of shelters by Akodon montensis were assessed using the spool-and-line technique. Movements of a few individuals of Thaptomys nigrita, Brucepattersonius iheringi and Oligoryzomys nigripes were also assessed and briefly described. Akodon montensis often used fallen logs, lianas and ferns as climbing supports for movements. The species moved under different environmental structures with differing frequencies, with greater use of dense litter f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Although we did not examine the microhabitat (i.e., station-level) associations for each species in this study, we previously reported that A. montensis was positively associated with fallen branches, while O. nigripes was not associated with any particular microhabitat characteristic [ 47 ]. A. montensis use fallen branches for shelter and nesting, which could provide an explanation to why more rodents were found on the least degraded grids [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not examine the microhabitat (i.e., station-level) associations for each species in this study, we previously reported that A. montensis was positively associated with fallen branches, while O. nigripes was not associated with any particular microhabitat characteristic [ 47 ]. A. montensis use fallen branches for shelter and nesting, which could provide an explanation to why more rodents were found on the least degraded grids [ 132 ].…”
Section: Discussionmentioning
confidence: 99%